Measurement Methods and Application Research of Triple Helix Model in Collaborative Innovation Management - Xu, Hai-Yun; Zeng, Rong-Qiang; Fang, Shu; Yue, Zeng-Hui; Han, Zheng-Biao (Qualitative and Quantitative Methods in Libraries; Vol 4 No 2 (2015): June 2015 Issue, 2017)
Abstract: In the knowledge economy era, the innovation body is formed into Government-Industry -Academy collaborative innovation pattern, which can be described by triple helix model. What’s more, triple helix model can better serve the scientific and technological innovation management. Although a variety of triple helix measurement methods have been applied into evaluation practice, these methods have their own drawbacks. In this paper, we conducted an in-depth analysis on the current principal methods based on mathematical characteristics. Combined with empirical analysis, we expect to form a comprehensive utilization pattern of different methods. This paper discusses the theory development of triple helix model with a focus on measurement methods, which are method based on mutual information and method cooperation similarity respectively. In this paper, we summarize the application scope of triple helix model by means of output of scientific papers, and bring technology transfer organization (TTO) into the triple helix innovation dimension, which can provide the triple helix model with exogenous motivation. Finally, we make a discussion on the future improvements of the triple helix model.